Extremes in Nature An Approach Using Copulas - Salvadori, Gianfausto; De Michele, Carlo; Kottegoda, Nathabandu T.; Rosso, Renzo (Water Science and Technology Library, 2007)
The study of the statistics of extreme events is an essential first step in the mitigation of natural catastrophies, that often cause severe economic losses worldwide. This book is about the theoretical and practical aspects of the statistics of Extreme Events in Nature. Most importantly, this is the first text in which Copulas are introduced and used in Geophysics. Several topics are fully original, and show how standard models and calculations can be improved by exploiting the opportunities offered by Copulas. In addition, new quantities useful for design and risk assessment are introduced. Practicioners in all research areas of Geosciences and extreme events (including Finance and Insurance, closely related to natural disasters) will definitely benefit from the new Copula-approach outlined in the book. Audience This volume will be of interest to researchers and practitioners in the fields of civil and environmental engineering, geophysics, geosciences, geography and environmental science. Also scientists and undergraduate up to post graduate level students in water resources and hydrology will find valuable information in this book.